Characterization of low molecular weight sulfur species in seaweed from the Antarctic continent - Soares Rondan, Filipe; Pisarek, Paulina; Bernabeu de Maria, Mikel; Szpunar, Joanna; Mesko, Marcia Foster (Analytical and Bioanalytical Chemistry, 2024)
International audience Antarctic seaweeds are vital components of polar marine ecosystems, playing a crucial role in nutrient cycling and supporting diverse life forms. The sulfur content in these organisms is particularly interesting due to its implication in biogeochemical processes and potential impacts on local and global environmental systems. In this study, we present a comprehensive characterization of seaweed collected in the Antarctic in terms of their total sulfur content and its distribution among different classes of species, including thiols, using various methods and high-sensitivity techniques. The data presented in this paper are unprecedented in the scientific literature. These methods allowed for the determination of total sulfur content and the distribution of sulfur compounds in different fractions, such as water-soluble and proteins, as well as the speciation of sulfur compounds in these fractions, providing valuable insights into the chemical composition of these unique marine organisms. Our results revealed that the total sulfur concentration in Antarctic seaweeds varied widely across different species, ranging from 5.5 to 56 g kg−1 dry weight. Furthermore, our investigation into the sulfur speciation revealed the presence of various sulfur compounds, including sulfate, and some thiols, which were quantified in all ten seaweed species evaluated. The concentration of these individual sulfur species also displayed considerable variability among the studied seaweeds. This study provides the first in-depth examination of total sulfur content and sulfur speciation in brown and red Antarctic seaweeds. Graphical abstract: (Figure presented.)